The globalization of American criminal justice: The New Zealand Case: - Martin, Liam (The Australian and New Zealand journal of criminology, 2018)
The international influence of American criminal justice policy has been a central focus of research on policy transfer and comparative penology. With scholars divided between those emphasizing international convergence around United States policy, and others stressing ongoing American exceptionalism, it has become important to trace the extent of this influence not only across different countries but within particular national contexts. This article examines the impact of American criminal justice policy in New Zealand. I present three case studies exploring developments in different arms of the criminal justice system: the introduction of three strikes sentencing laws, the adoption of supermax principles of prison design and administration, and the use of zero tolerance and broken windows policing strategies. In tracing these changes, I find globalization opening new channels for the movement of policy that are often outside the control of the criminal justice establishment.